2013
DOI: 10.1158/1078-0432.ccr-13-0542
|View full text |Cite
|
Sign up to set email alerts
|

A 26-Gene Hypoxia Signature Predicts Benefit from Hypoxia-Modifying Therapy in Laryngeal Cancer but Not Bladder Cancer

Abstract: Purpose: Tumor hypoxia is associated with a poor prognosis, hypoxia modification improves outcome, and hypoxic status predicts benefit from treatment. Yet, there is no universal measure of clinical hypoxia. The aim of this study was to investigate whether a 26-gene hypoxia signature predicted benefit from hypoxiamodifying treatment in both cancer types.Experimental Design: Samples were available from 157 T2-T4 laryngeal cancer and 185 T1-T4a bladder cancer patients enrolled on the accelerated radiotherapy with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
223
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(228 citation statements)
references
References 34 publications
4
223
1
Order By: Relevance
“…To date, the potential of hypoxia gene signatures to discriminate pretreatment tumor specimen regarding their hypoxiainduced gene expression levels has not been tested in the postoperative setting (15,16,18). However, there is some evidence from an experimental study of our laboratory, which showed that pretreatment hypoxia impacts local tumor control after radiotherapy also when radiotherapy was applied under homogenous anoxic conditions (20).…”
Section: Translational Relevancementioning
confidence: 99%
See 4 more Smart Citations
“…To date, the potential of hypoxia gene signatures to discriminate pretreatment tumor specimen regarding their hypoxiainduced gene expression levels has not been tested in the postoperative setting (15,16,18). However, there is some evidence from an experimental study of our laboratory, which showed that pretreatment hypoxia impacts local tumor control after radiotherapy also when radiotherapy was applied under homogenous anoxic conditions (20).…”
Section: Translational Relevancementioning
confidence: 99%
“…Samples were then kept at 4 C for a maximum of 18 hours and subjected to the nCounter system and processed as described elsewhere (27). Raw counts were logarithmized and then normalized to the mean of the internal level of reference genes ACTR3, NDFIP1, RPL37A, B2M, GNB2L1, RPL11, POLR2A or to the reference genes of the corresponding hypoxia gene signatures (Supplementary Table S1B), respectively (15,16). cDNA generation and RT-PCR RNA was converted to cDNA using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Life Technologies).…”
Section: Nanostring Analysesmentioning
confidence: 99%
See 3 more Smart Citations